A Study on Assessment of Impact of Home Confinement and Associated Risk Factors During COVID-19 Lockdown Among Disabled Children in Chennai District, Tamil Nadu- A Cross-Sectional Study - BN, Surya; Balaann, Krishnaprasanth; Ramachandran, Umadevi; VM , Anantha Eashwar; RJ Charulatha; Pragadeesh P (National Journal of Community Medicine, 2023)
Introduction: The home confinement imposed due to the coronavirus disease (COVID-19) pandemic has dispro-portionally affected the lives of children around the globe, particularly children with pre-existing vulnerabilities. The study assessed the impact of home confinement and the associated risk factors among disabled children re-siding in the Chennai district, during the COVID-19 lockdown. Methods: The list of special schools in Chennai were collected, and five special schools were randomly chosen by lottery method. Using simple random sampling technique children were selected till the required sample size of 189 was reached. Semi-structured questionnaire was used for data collection. Informed consent was obtained, and data was entered in MS Excel and analyzed by SPSS version 22. Results: Among the study participants around 64% had an impact due to home confinement during the covid lockdown. Statistically significant predictors (p-value <0.05) of home confinement due to Covid-19 were anger & frustration (AOR - 6.47, 95% CI – 2.5-12.6), increased crying among children (AOR - 4.89 95% CI – 1.7-8.5) and sleep disturbances (AOR - 2.92, 95% CI – 1.8-7.1). Conclusion: Increased care and attention needs to be provided to disabled children as they are more prone to get affected due to lockdown restrictions.